2016
DOI: 10.1021/acs.jmedchem.6b01167
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in the Development of Serine Synthetic Pathway Inhibitors for Cancer Therapy

Abstract: Recent advances in the understanding of the relationship between cancer and metabolism have highlighted the relevance of the serine synthetic pathway (SSP), which consists of three successive enzymatic reactions. Enzymes of the SSP, such as phosphoglycerate dehydrogenase (PHGDH) and phosphoserine aminotransferase 1 (PSAT-1), were recently highlighted because they are amplified in a significant subset of human tumors, and their suppression by RNAi caused a decrease in cancer cell survival and growth. Currently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…The oncogenic role and prognostic value of PHGDH, which catalyzes the first rate‐limiting step in serine biosynthesis, has been investigated in multiple cancer types, including breast cancer, melanoma, cervical cancer, and colon cancer, as well as lung cancer . An analysis of a large panel of NSCLC cell lines also revealed that NRF2 (not detected in this study) controls PHGDH expression, which confers poor prognosis in NSCLC patients . We identified a significantly high expression at the protein levels of PHGDH and also SHMT2 (FC, 5.68; p < 0.0001), by which serine can be converted into glycine, in tumor cells of SCLC patients.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The oncogenic role and prognostic value of PHGDH, which catalyzes the first rate‐limiting step in serine biosynthesis, has been investigated in multiple cancer types, including breast cancer, melanoma, cervical cancer, and colon cancer, as well as lung cancer . An analysis of a large panel of NSCLC cell lines also revealed that NRF2 (not detected in this study) controls PHGDH expression, which confers poor prognosis in NSCLC patients . We identified a significantly high expression at the protein levels of PHGDH and also SHMT2 (FC, 5.68; p < 0.0001), by which serine can be converted into glycine, in tumor cells of SCLC patients.…”
Section: Discussionmentioning
confidence: 52%
“…Tumors have exceptionally high energetic and anabolic requirements due to rapid cell growth and proliferation, and the serine biosynthetic pathway was recently identified as an important source of metabolic intermediates for these processes. The oncogenic role and prognostic value of PHGDH, which catalyzes the first rate‐limiting step in serine biosynthesis, has been investigated in multiple cancer types, including breast cancer, melanoma, cervical cancer, and colon cancer, as well as lung cancer . An analysis of a large panel of NSCLC cell lines also revealed that NRF2 (not detected in this study) controls PHGDH expression, which confers poor prognosis in NSCLC patients .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In human PHGDH, the active site consists of the substrate-binding domain and nucleotide domain. It is lined by several loop regions of the first monomers Arg54-Val59, Ala76-Val83, Asn97-Gly101, Gly152-Leu153, Asp175-Ile178, His206-Leu216, Cys234-Val240, Asp260-Asp269, and Cys281-Ser287 and one loop of the second monomer Trp133-Lys136 [29].…”
Section: The Type and Structure Of 3-phosphoglycerate Dehydrogenasementioning
confidence: 99%
“…[1][2] Given PHGDH's potential as a drug target in certain cancers, a number of PHGDH inhibitors have been reported. [3][4][5][6][7][8][9][10][11] AstraZeneca used a fragment-based lead discovery approach followed by medicinal chemistry optimization to develop an indole derivative ( Figure 1) with submicromolar K D . [4][5] Cantley and colleagues used a biochemical high-throughput screen to identify a PHGDH inhibitor (CBR-5884, Figure 1) with an IC 50 of ~33 μM.…”
Section: Introductionmentioning
confidence: 99%